If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 25 = x Reorder the terms: 25 + 5x = x Solving 25 + 5x = x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 25 + 5x + -1x = x + -1x Combine like terms: 5x + -1x = 4x 25 + 4x = x + -1x Combine like terms: x + -1x = 0 25 + 4x = 0 Add '-25' to each side of the equation. 25 + -25 + 4x = 0 + -25 Combine like terms: 25 + -25 = 0 0 + 4x = 0 + -25 4x = 0 + -25 Combine like terms: 0 + -25 = -25 4x = -25 Divide each side by '4'. x = -6.25 Simplifying x = -6.25
| 25=x-5x | | 2(x+5)=-2x-10 | | y=6x+3x | | 6x+2y+4=0 | | 15x*12x= | | 0-4(0)=2 | | i*z^2+8=0 | | 3(4)-6/x/12 | | 24=25x+12 | | x^2=3x+32 | | ox^2-21=-5 | | -8-7r=-(-7+2r) | | 5m+7=2m+1 | | 10(d+7)=2(d-5)+8d | | (0.15)x+(0.20)=0.16(x+25) | | cos(2x)-cos(3x)+cos(4x)=0 | | 5x-3x+6=-10-2 | | -2168+271m=0 | | km/3-2x=4 | | 32y^5-80y^2+50y=0 | | 2p+3q=37 | | -3-3h=48 | | 42x/6×x^8/7x^5 | | 3(n+7)=3-3(n-2) | | (2y-7)(4+y)=0 | | 36a^2+6ax=0 | | 2cosx+tanx=secx | | 3(x+5)=2(x-7) | | 14x(-10)= | | 5(2x)=1/25 | | 12x+72=4(x-6) | | -z-17=-6z+3 |